Association among serum per- and polyfluoroalkyl substances, lipid profile and metabolic syndrome in Czech adults, HBM-EHES survey 2019 - Puklová, Vladimíra; Čapková, Naďa; Fialová, Alena; Vavrouš, Adam; Žejglicová, Kristýna; Černá, Milena (Central European journal of public health, 2023)
OBJECTIVES: Per- and polyfluoroalkyl substances (PFASs) are a large group of persistent synthetic chemicals widely used commercially. They accumulate increasingly in all environmental components and enter the organisms, including humans. Some of them are associated with the risk of harm to health, among others with metabolic disorders. To test the associations between blood serum levels of PFASs and blood lipid profile as well as metabolic syndrome, we linked human biomonitoring with the Czech Health Examination Survey (CZ-EHES) conducted in 2019. METHODS: A total of 168 participants of the CZ-EHES survey aged 25-64 years were examined including anthropometrical data and analyses for serum PFAS and blood lipid levels. Extended model approach in multiple linear regression models was used for identification of the associations between serum levels of 11 PFASs and lipid profile components. The relation between PFAS serum levels and metabolic syndrome prevalence was tested using a logistic regression model. RESULTS: Six PFASs were detected over the limit of quantification in at least 40% cases and were examined in subsequent analyses: perfluorodecanoic acid (PFDA), perfluorohexane sulfonic acid (PFHxS), perfluorooctanoic acid (PFOA), perfluorononanoic acid (PFNA), perfluorooctane sulfonic acid (PFOS), perfluoroundecanoic acid (PFUdA). The most dominant was PFOS with the mean value amounting to 4.81 ng/ml. After adjusting for potential confounders, we found a significant positive association between serum PFHxS and blood total cholesterol (p = 0.005) as well as LDL-cholesterol (p = 0.008). Significant positive association was also found between PFDA and HDL-cholesterol levels (p = 0.010). No significant associations were detected between PFASs and triglycerides, and between PFASs and metabolic syndrome. CONCLUSIONS: We found some evidence of a significant association between blood serum PFAS levels and blood cholesterol levels. Our results did not confirm an association between serum PFASs and the metabolic syndrome prevalence.
Keywords: Cholesterol; kyseliny sulfonové; Humans; cholesterol; Alkanesulfonic Acids; dospělí; lipidy; kyseliny dekanové; lidé; látky znečišťující životní prostředí; metabolický syndrom; Serum; Adult; Sulfonic Acids; Environmental Pollutants; Metabolic Syndrome; sérum; Czech Republic; Lipids; fluorokarbony; Česká republika; Fluorocarbons; Decanoic Acids; kyseliny alkansulfonové